"Mi raza primero!" (My people first!) : nationalism, identity, and insurgency in the Chicano movement in Los Angeles, 1966-1978 - Chávez, Ernesto, 1962- (University of California Press, 2002)
"!Mi Raza Primero! is the first book to examine the Chicano movement's development in one locale-in this case Los Angeles, home of the largest population of people of Mexican descent outside of Mexico City. Ernesto Chavez focuses on four organizations that constituted the heart of the movement: The Brown Berets, the Chicano Moratorium Committee, La Raza Unida Party, and the Centro de Accion Social Autonomo, commonly known as CASA. Chavez examines and chronicles the ideas and tactics of the insurgency's leaders and their followers who, while differing in their goals and tactics, nonetheless came together as Chicanos and reformers. Deftly combining personal recollection and interviews of movement participants with an array of archival, newspaper, and secondary sources, Chavez provides an absorbing account of the events that constituted the Los Angeles-based Chicano movement. At the same time he offers insights into the emergence and the fate of the movement elsewhere. He presents a critical analysis of the concept of Chicano nationalism, an idea shared by all leaders of the insurgency, and places it within a larger global and comparative framework. Examining such variables as gender, class, age, and power relationships, this book offers a sophisticated consideration of how ethnic nationalism and identity functioned in the United States during the 1960s and 1970s."--